A base-stable metal-organic framework for sensitive and non-enzymatic electrochemical detection of hydrogen peroxide. (1st June 2018) - Lopa, Nasrin Siraj; Rahman, Md. Mahbubur; Ahmed, Faiz; Chandra Sutradhar, Sabuj; Ryu, Taewook; Kim, Whangi
Abstract: Stability of metal-organic frameworks (MOFs) in aqueous medium and extreme solution conditions (acidic or basic) are important for the development of stable, reproducible, and sensitive electrochemical biosensors. Herein, a base-stable chromium(III) dicarboxylate MOF was synthesized by microwave assisted solvothermal method for non-enzymatic detection of hydrogen peroxide (H2 O2 ). The as-synthesized MOF exhibited excellent base stability without any obvious changes in crystallinity, morphology, and spectroscopic behaviors after base treatment. This MOF-modified glassy carbon electrode showed negligible change in charge transfer resistance at the electrode|electrolyte interface after redox cycling and good catalytic activity for the reduction of H2 O2 in 0.1 M NaOH(aq.) . The enhanced catalytic activity of H2 O2 reduction is enabled by the redox process of Cr III/II in the chromium (III) dicarboxylate. The sensor showed the sensitivity of ca. 11.9 μA mM −1, wide linear range from 25 to 500 μM, and a method detection limit of ca. 3.52 μM. The validation of this sensing platform was evaluated by standard addition method. Thus, the present biosensor could be used for the point of care detection of H2 O2 . Graphical abstract: Image 1 Highlights: A Cr-MOF (MIL-53-Cr III ) was utilized for H2 O2 sensing for the first time. The Cr-MOF exhibits high chemical and electrochemical stability in NaOH solution. The redox processes of Cr III/II in MIL-53-Cr III have induced the direct reduction of H2 O2 . The sensor shows a wide linear range, good sensitivity, and low method detection limit.